Evaluating interior design of selected UP Diliman student lounges in terms of functionality and comfort - Famillaran, Steffe Marie N.; Ong, Charlene Dominique Y.; Rubio, Shane Nicole A.
In higher education, informal learning spaces like student lounges are crucial for academic engagement, collaboration, and student well-being. At UP Diliman, despite efforts to develop such lounges, these spaces often remain overcrowded and insufficient. This study evaluated the functionality and comfort of three UP Diliman student lounges: (1) The Third Space, (2) the Institute of Civil Engineering (ICE) Student Lounge, and (3) the UP School of Economics (UPSE) Student Lounge. The researchers aimed to describe their interior design, examine the application of relevant strategies, identify student preferences, and assess the alignment between current designs and student needs. Using a convergent parallel design, both qualitative and quantitative data were gathered through ocular inspections, a survey of 92 undergraduate students, and follow-up interviews with three (3) selected respondents. Guided by the Onion Theory of Comfort (Rybczynski, 1986) and User-Centered Design Theory (Vischer, 2008), the study found that while these lounges are visually inviting and align with general student preferences, functional aspects are less positively perceived. Students tended to overlook minor inconveniences, suggesting a level of tolerance rather than complete satisfaction. This partial alignment between current designs and student preferences highlights the need for design improvements. The study concludes that physical comfort alone is insufficient. It emphasizes the necessity of proactive, user-centered design approaches that incorporate explicit user feedback throughout the design process. This ensures the creation of more effective and supportive student spaces by addressing both physical and functional elements, leading to the development of truly user-centered student lounges.